Social support, health and oral health promotion in the elderly population in Brazil - Silvânia Suely Caribé de Araújo; Danielle Bianca de Lima Freire; Dalva Maria Pereira Padilha; Julio Baldisserotto; Cássio Murilo Pereira (Faculdade de Medicina de Botucatu (Unesp), 2006)
The world people increasing aging, including Brazil, emphasizes the importance of measure to deal with this situation. In Brazil, the majority of elderly is woman, lives in houses with other generations, is economic reference in these houses, is in the low economic level, has at least one chronic disease, is independent to do daily life activities, doesn't have teeth, and look for health care services in the Unified National Health System (SUS). Brasilian elderly have exposed the social vulnerability situations, they are submited to direct interference of the social determinants in the health-disease process. The Social Support includes social policies and networks, that plays a role the agent to join the elder and the society, it is decreasing the risks of social exclusion and consequently the damages to his/her health through Health Promotion measurements. This article concerns the Social Support and some of its aspects like: Type and place of residence, Transport and Financial Support; in Brazilian elderly and its relation between the Health Promotion.